2020
DOI: 10.1002/ccd.29369
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year clinical outcomes with the ABSORB bioresorbable vascular scaffold in real life: Insights from the France ABSORB registry

Abstract: Objectives: The aim of this study was to determine the 3-year outcomes of patients treated with Absorb bioresorbable vascular scaffold (BVS) implantation.Background: Randomized trials and observational registries performed in patients undergoing percutaneous coronary intervention have demonstrated higher 1-year and midterm rates of device thrombosis and adverse events with BVS compared to contemporary drug eluting stent. Data on long-term follow-up of patients treated with BVS are scarce.Methods: All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In one such study, it was found that biodegradable alloy based vascular implants showed minimal/moderate acute toxicity as well as favorable physiological degradation [ 11 , 12 ], the Xinsorb BRS is at the forefront of technological innovation [ 13 ], while Lepu Medical's NeoVas BRS has recently been approved for clinical use in China [ 5 , 14 ]. Further clinical trials on BVS and Xinsorb revealed acceptable target vessel-related myocardial infarction but without discussion on degradation induced phenotype and functions of vascular cells [ [15] , [16] , [17] ]. The implantation of AMsorb™ BRS, a 3-D printed PLLA scaffold, showed that complete reendothelializations could be achieved within 90 days with no thrombus formation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one such study, it was found that biodegradable alloy based vascular implants showed minimal/moderate acute toxicity as well as favorable physiological degradation [ 11 , 12 ], the Xinsorb BRS is at the forefront of technological innovation [ 13 ], while Lepu Medical's NeoVas BRS has recently been approved for clinical use in China [ 5 , 14 ]. Further clinical trials on BVS and Xinsorb revealed acceptable target vessel-related myocardial infarction but without discussion on degradation induced phenotype and functions of vascular cells [ [15] , [16] , [17] ]. The implantation of AMsorb™ BRS, a 3-D printed PLLA scaffold, showed that complete reendothelializations could be achieved within 90 days with no thrombus formation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%